Cyber ethnography: A critical tool for the Department of Defense?. Issue 2 (14th March 2016) - Black, Michelle
Abstract: There seems to be a current push for intelligence to be more informed through sociocultural analysis. This article argues that a new variation of ethnography, cyber ethnography, is the answer to calls for additional support, and should be incorporated into the Department of Defense (DoD) methodological "tool box." This article answers: What is cyber ethnography and how could it contribute to United States defense work? What are some of the method's limitations and challenges, especially when performed by DoD personnel? At the same time, what type of community could be studied by the DoD using cyber ethnography? And finally, what are the requirements to perform this method?